Edukasi Dengan Media Permainan Ular Tangga Terhadap Pengetahuan Kebersihan Gigi Dan Mulut Pada Siswa Sekolah Dasar - Nova Ghea, Pinky (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
The use of attractive media is needed to increase the knowledge of elementary school children regarding dental and oral hygiene. The selection of media needs to be tested to increase knowledge. The purpose of this study was to determine the effectiveness of education with the Snake Ladder Game media on the knowledge of dental and oral hygiene in elementary school students at Muhammadiyah 2 Elementary School in Pontianak. The research used is Quasi Experiment with Pre and Posttest Group. The number of samples was 40 students from class IV A. This study was conducted for 5 consecutive days in July. The results showed that the provision of education with game media, The Snake and Ladders of Muhammadiyah 2 Elementary School Pontianak in the experimental group students increased their knowledge more significantly than the control group who were not given intervention. This is evidenced by students' knowledge scores of the experimental group before 52.25 intervention increased to 89.25 with P value = 0,000 while the pretest control group 52.25 increased to 55.25 with P value = 0.137. Based on the results of the study, it was suggested to the relevant agencies to adopt dental and oral hygiene intervention models by giving the Snakes Ladder Game media to students to improve students' knowledge about dental and oral hygiene in elementary school students.